Proposta de texto dissertativo-argumentativo e autoria - Bristot, Sílvia Letícia Duarte Scopel (2010)
This study pretend to investigate the textual production, in the gender dissertateargumentative, by students graduating at high school, and potential candidates in selection processes for entry to Higher Education. The objective was to know if the text proposition interferes with the argumentative orientation held by the student, in your text. The linguistic theory that guided the research is the ADL, in its most recent form, Blocks Semantic Theory. Under the support of this theory, the methodology consisted of using the proposed text at 2005 edition of the National Examination of High School - ENEM apply it in its entirety for a particular class. The two other classes had access to one of the stimulus texts contained in the proposal, but taking the issue Childish Labor under contrary optical. The survey results show that the proposed text does not interferes decisively in the direction of argument defend by the student, because, for most cases, what is lacking is the ability to read, to seize reason with the proposed text, and then, with it agree, or refute it. There was also the conclusion that the concept of authorship within the limits of the ADL - TBS seems to be the ability to create innovative linkages between predicates whose meanings are already crystallized in the language